Performance of solar funnel cookers using intermediate temperature test load under low sun elevation - Apaolaza-Pagoaga, Xabier; Sagade, Atul; Rodrigues-Ruivo, Celestino; Carrillo-Andrés, Antonio (Elsevier, 2021)
Solar funnel cookers can be designed as attractive and affordable low-cost devices accessible to people in all continents of the world regardless of their walk-in life. The present work is aimed to investigate the applicability of funnel cookers to attain the temperature in excess of the boiling point of water. It widens their acceptability for cooking and opens new opportunities for technological developments in such designs of solar cookers. Two identical designs of funnel cookers, FC1 and FC2, have been tested with appropriately sized identical cooking pots and glass enclosure to serve the purpose. Cooker FC2 is tested with a glass enclosure only, while a glass enclosure is not used in FC1. Glycerine is used as a test load. Cooker Opto-thermal Ratio (COR) as a thermal performance parameter and overall cooking efficiency are used to compare the performance of the two funnel cookers. It is shown that the temperature of the test load in the cooker FC2 can reach 140 to 150 ◦C. So, this funnel cooker design can be preferred for cooking food at a relatively high temperature over the boiling point of water. The experimental results show that: i) the mean values of the Cooker Opto-thermal Ratio for cookers FC2 and FC1 are estimated to be 0.157 and 0.110 (m2◦C)/W, respectively, and ii) the values of the overall cooking efficiency for cookers FC2 and FC1 are estimated to be 11.8% and 10.2%, respectively.
Keywords: Energía solar - Aplicaciones; Solar funnel cookers; Sustainable development goals; Intermediate temperature cooking; Portable solar cookers; Clean and sustainable cooking